PERAN INTERGOVERNMENTAL AUTHORITY ON DEVELOPMENT (IGAD) DALAM PEMBAGIAN KEKUASAAN DI SUDAN SELATAN MELALUI REVITALIZED AGREEMENT ON THE RESOLUTION OF THE CONFLICT OF SOUTH SUDAN (R-ARCSS) - Christina, Eunike; Putri, Penny Kurnia; Parameswari, A.A.A Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
South Sudan is a country that just gained its independence in 2011. But not long after its independence, there was a protracted civil war. IGAD as a sub-regional organization has the responsibility to maintain peace in the Horn of Africa region. Therefore, the R-ARCSS was published as a peace agreement that will be a guide in the peacebuilding process. This study uses the concept of international organizations as actor and the concept of peacebuilding to explain the role of the IGAD organization in the power-sharing process which also includes efforts to build peace. This study uses a descriptive qualitative method by collecting data which is then interpreted and adapted to the concepts used to answer the problem formulation. From this research, it appears that IGAD has a big influence on the implementation of R-ARCSS. Some of the things that IGAD did were to establish several institutions in accordance with the R-ARCSS, assist in improving communication between parties who were previously in conflict, and monitor and evaluate the implementation of the R-ARCSS. Keywords : IGAD, International Organization, Peacebuilding, South Sudan.